2020
DOI: 10.3389/fnint.2020.534595
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Manipulative Therapy Alters Brain Activity in Patients With Chronic Low Back Pain: A Longitudinal Brain fMRI Study

Abstract: Background: Spinal manipulative therapy (SMT) helps to reduce chronic low back pain (cLBP). However, the underlying mechanism of pain relief and the neurological response to SMT remains unclear. We utilized brain functional magnetic resonance imaging (fMRI) upon the application of a real-time spot pressure mechanical stimulus to assess the effects of SMT on patients with cLBP. Methods: Patients with cLBP (Group 1, n = 14) and age-matched healthy controls without cLBP (Group 2, n = 20) were prospectively enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…25 Following the relief of pain after the first SMT, the Reho values of the left precuneus were increased and there was no longer any statistical difference with healthy controls, which implies a restoration of the dysfunction in the DMN. In the study of Tan et al, 17 the left precuneus in patients with CLBP also showed increased activity in response to the mechanical stimulus of the low 194 back area after the first SMT, compared to healthy control. So the left precuneus appears to play a key role in the maintenance of CLBP and mediates the restoration of brain function after the first SMT in patients with CLBP.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…25 Following the relief of pain after the first SMT, the Reho values of the left precuneus were increased and there was no longer any statistical difference with healthy controls, which implies a restoration of the dysfunction in the DMN. In the study of Tan et al, 17 the left precuneus in patients with CLBP also showed increased activity in response to the mechanical stimulus of the low 194 back area after the first SMT, compared to healthy control. So the left precuneus appears to play a key role in the maintenance of CLBP and mediates the restoration of brain function after the first SMT in patients with CLBP.…”
Section: Discussionmentioning
confidence: 85%
“…16 Our previous research showed that SMT changed the mode of patients with CLBP when responding to press stimulus in the spinal area. 17 However, whether SMT can change brain activity at rest, and whether there may be correlations between these potential changes with clinical symptoms has not been studied. Hence, we enrolled patients with CLBP in this prospective study and analyzed the changes of brain activity at rest, immediately after the first SMT and after six courses of SMT, to explore the immediate and long-term central analgesia mechanism of SMT.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, brain functional magnetic resonance imaging showed that the brain functional activity was mainly inhibited, and the inhibitory area was mainly located in the right prefrontal lobe and cerebellum, indicating that tuina may relieve pain by inhibiting the functional activities of the frontal lobe and cerebellum. Tan et al (2020) found that the brain activity in the right parahippocampal gyrus, the right dorsolateral prefrontal cortex, and the left precuneus was significantly increased after one time of spinal manipulative treatment, and the brain activity in the posterior cingulate cortex (PCC) and right inferior frontal gyrus was significantly increased after six times of treatment.…”
Section: Tuina Exerts Analgesic Effects By Adjusting the Functional A...mentioning
confidence: 99%
“…Identifying specific regions involved in chronic pain and those related to each other, even if nonspecific, as well as the study of the development of pain and comorbidities associated with functional neuroimaging techniques, can allow the development of future target therapies (Tan et al 2020 ; Isenburg et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%